2022
DOI: 10.1037/men0000385
|View full text |Cite
|
Sign up to set email alerts
|

Extending the gender role strain paradigm to account for U.S. males’ gun violence.

Abstract: Most gun violence is committed by males, yet most males do not commit acts of gun violence, indicating that some aspect of masculinity that varies among males might account for this incongruence. I proposed that masculine gender role discrepancy strain, in combination with acquired capacity for gun violence, might account for why some boys and men commit acts of gun violence. The evidence for the role of discrepancy strain in the perpetration of violence was reviewed, with support coming from correlational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…Additional attributes of hegemonic masculinity include a normalization of violence, especially if said violence is viewed as a means to achieve or prove one's power and dominance, the belief that women are inferior to men and thus are deserving of a subordinate position in society, and the preoccupation with and sense of entitlement to sex (Connell, 1987;Levant et al, 2010), all of which were frequently observed within shooters' histories and are correlates of VAW. Furthermore, in line with recent research on masculinity and gun violence (Borgogna et al, 2022;Levant, 2022;O'Dea et al, 2022), almost all profiled shooters had a documented history of threatened masculinity. Consistent with masculine gender role discrepancy strain (Pleck, 1981) and precarious manhood (Vandello et al, 2008), when men are unable to meet the expectations of hegemonic masculinity, they may experience intense stress and respond to this stress in ways consistent with hegemonic masculinity, such as through the use of violence, to prove their manhood.…”
Section: Violence Against Women and School Shootingssupporting
confidence: 58%
See 2 more Smart Citations
“…Additional attributes of hegemonic masculinity include a normalization of violence, especially if said violence is viewed as a means to achieve or prove one's power and dominance, the belief that women are inferior to men and thus are deserving of a subordinate position in society, and the preoccupation with and sense of entitlement to sex (Connell, 1987;Levant et al, 2010), all of which were frequently observed within shooters' histories and are correlates of VAW. Furthermore, in line with recent research on masculinity and gun violence (Borgogna et al, 2022;Levant, 2022;O'Dea et al, 2022), almost all profiled shooters had a documented history of threatened masculinity. Consistent with masculine gender role discrepancy strain (Pleck, 1981) and precarious manhood (Vandello et al, 2008), when men are unable to meet the expectations of hegemonic masculinity, they may experience intense stress and respond to this stress in ways consistent with hegemonic masculinity, such as through the use of violence, to prove their manhood.…”
Section: Violence Against Women and School Shootingssupporting
confidence: 58%
“…Furthermore, some have identified gun violence as one avenue to perform masculinity. Levant (2022) theorized the role of “threatened masculinity” (encompassing gender role discrepancy strain and precarious manhood, as well as other related constructs) in gun violence among men, including school shootings, particularly highlighting the role of internalized shame. He states, “Boys who were treated this way [punished for violating masculine norms] might grow up to be men for whom a threat to their masculinity is just unbearable and requires an extreme forceful response, such as gun violence” (p. 158).…”
Section: Defining Violence Against Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…When we apply this framework to a highly salient social category like gender, the ought-self becomes a powerful predictor of individual self-concept and behavior. Extensive research has documented the detrimental effects that other-imposed masculinity expectations can have on boys and men (Levant, 2011(Levant, , 2022Levant & Richmond, 2016;Rummell & Levant, 2014), and we situate this past work in self-discrepancy theory as a cohesive framework in explaining the antecedents and consequences of men's differential motivations to be stereotypically masculine.…”
Section: Self-discrepancy Theory and Masculine Identity Discrepancymentioning
confidence: 99%
“…Gender role discrepancy strain is one form of gender role strain which has received particular attention in previous work, and is theorized to emerge within contexts where people behave, think, feel, or are perceived in ways that are discrepant from gender role expectations (Levant & Powell, 2017;Pleck, 1981Pleck, , 1995. Person-level differences in the propensity to experience gender role discrepancy strain are commonly assessed using measures of gender role stress (Levant, 2022;Levant & Powell, 2017;Pleck, 1995). Gender role stress indexes the degree to which women and men experience stress in gender role discrepant contexts, such as when men fail to possess power or women fail to be nurturant or attractive (Eisler & Skidmore, 1987;Gillespie & Eisler, 1992).…”
mentioning
confidence: 99%